2011
DOI: 10.5326/jaaha-ms-5676
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method of Core Aspirate Cytology Compared to Fine-Needle Aspiration for Diagnosing Canine Osteosarcoma

Abstract: There is little information in veterinary literature regarding the diagnostic accuracy of aspirate cytology for the diagnosis of canine osteosarcoma (OSA). The authors compared the diagnostic accuracy of a novel method of cytologic collection, termed core aspirate cytology (CA), with fine needle aspiration (FNA) and histopathology in 27 dogs with lytic and/or proliferative bone lesions. Alkaline phosphatase (ALP) staining was performed to confirm the diagnosis of OSA cytologically. OSA was accurately diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…20,21 Similar studies in veterinary medicine reports accuracies between 97 and 69% in differentiating benign and malignant lesions. 11,15,22,23 Several elements partially limit the interpretation and comparison of the results with these studies. In some of those, the histologic diagnosis being compared with cytological diagnosis was indifferently obtained from surgical/post-mortem samples or from small incisional biopsies.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…20,21 Similar studies in veterinary medicine reports accuracies between 97 and 69% in differentiating benign and malignant lesions. 11,15,22,23 Several elements partially limit the interpretation and comparison of the results with these studies. In some of those, the histologic diagnosis being compared with cytological diagnosis was indifferently obtained from surgical/post-mortem samples or from small incisional biopsies.…”
Section: Discussionmentioning
confidence: 94%
“…The main limitation of these methods is that reactive osteoblasts will stain positive as well, so criteria of malignancy must be assessed. 15,[25][26][27] Overall, the concordance of cytology and histology with the final diagnosis was not completely satisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sensitivity of cytology for diagnosing histologically-confirmed osteosarcomas as sarcomas was high, ranging from 79.2% to 95.0%, and its specificity was 100% in three out of four studies. 4,[8][9][10] The sensitivity of cytology in identifying the exact histotype (i.e. providing a specific diagnosis of osteosarcoma rather than a generic diagnosis of sarcoma) was investigated only by Loukopoulos et al (2005) and Sabattini et al (2017), and it was found to be lower (25.0% and 42.9%, respectively).…”
Section: Appraisal Application and Reflectionmentioning
confidence: 99%